Comparison of physicochemical and umami characterization of aqueous and ethanolic Takifugu obscurus muscle extracts. (August 2021) - Wang, Wenli; Ning, Menghua; Fan, Yuxia; Liu, Xia; Chen, Gaole; Liu, Yuan
Abstract: Most umami substances were developed in aqueous extracts. In this study, we compared the molecular weight distributions and sensory characteristics of ethanol and aqueous Takifugu obscurus muscle extracts, and assessed their taste-related metabolites and peptide profile (<3 kDa) using nuclear magnetic resonance and nano liquid chromatography-mass spectrometry. The potential antioxidant peptide in ethanolic fraction was screened using Peptide Ranker, BIOPEP and quantum chemical simulations. The results indicated that 60% ethanolic extract fraction (60%-F) had the highest umami intensity and more palatable overall taste among all pufferfish extracts. It can be caused by more umami enhancing components such as Asp, Asn, Ala and 5′-AMP, and considerable umami-potential smaller peptides in 60%-F. 60%-F also showed an antioxidant activity, and several antioxidant peptides was screened. The present study indicated the relationship between extract solution and taste characterization, which provided more possibility for the exploitation of umami substances and screening potential activity peptides.